Comparison of pollen grain composition and quality of honey obtained from forest and rangeland sites in Arasbaran region - Mohammad Safi Ahmad Abad; Anoushirvan Shirvany; Parisa Panahi (تحقیقات جنگل و صنوبر ایران, 2017)
Beekeeping is one of the most important rural activities and honey is one of the most valuable by-products obtained from rangelands and some forest areas in Arasbaran region. The aim of this research was to compare the pollen grain composition and quality of honeys obtained from Vinaq (rangeland habitat) and Tazekand (forest habitat). Ten hives (10 per habitat) was established at the beginning of the flowering season in 2013. After three months, honey produced in the habitats were taken in August and was transferred to the laboratory for physico-chemical analysis and pollen identification. Pollen studies showed that the pollen grains of common hornbeam (Carpinus betulus L.) and Montpellier maple (Acer monspessulanum L.) was dominant pollen in Vinaq and Tazekand, respectively. Futhermore, the pollen grains of Lonicera iberica M. B. and Montpellier maple in Vinaq and pollen grains of Wild cherry (Cerasus avium (L.) Moench) in Tazekand were identified as companion species. According to the results of physico-chemical properties of honey samples, and particularly humidity, HMF, revival sugar, total sugar and sucrose, quality of honey obtained from forest was better than rangeland. These observations indicate that bees prefer to use of trees and shrubs pollen in compare to herbs.